Teachers as Material Developers: Investigating Strategies for Writing Instruction in a Digital Age - A. Kamariah; Sudding, Muhammad Fahri Jaya; Musdalifah; Sakkir, Geminastiti; Maharani, Sardian (ARRUS Journal of Social Sciences and Humanities, 2025)
This study explores the strategies employed by English language teachers in developing writing instructional materials within digitally enriched learning environments. Using a qualitative multiple case study design, six teachers from junior high, senior high, and vocational schools were observed and interviewed. Findings reveal that while all teachers perceive themselves as active material developers, their approaches vary based on their digital literacy, pedagogical beliefs, and access to technological infrastructure. A process-based writing approach is commonly applied, with digital tools such as Google Docs, Grammarly, Padlet, and Canva supporting different stages of instruction. Teachers selected tools based on usability, relevance to student needs, and contextual constraints. However, challenges such as limited preparation time, uneven student digital literacy, and lack of institutional support persist. The study affirms the relevance of the Technological Pedagogical Content Knowledge (TPACK) framework. It highlights the need for professional development that equips teachers with skills to design pedagogically meaningful digital writing tasks.